Molecular Characterization and Function Analysis of the Vitellogenin Receptor from the Cotton Bollworm, Helicoverpa armigera (Hübner) (Lepidoptera, Noctuidae). - Wanna Zhang; Long Ma; Haijun Xiao; Bingtang Xie; Guy Smagghe; Yuyuan Guo; Gemei Liang (PLoS ONE, 2016)
Developing oocytes accumulate plentiful yolk protein during oogenesis through receptor-mediated endocytosis. The vitellogenin receptor (VgR), belonging to the low-density lipoprotein receptor (LDLR) family, regulates the absorption of yolk protein. In this work, the full-length vitellogenin receptor (HaVgR) in the cotton bollworm Helicoverpa armigera was identified, encoding a 1817 residue protein. Sequence alignment revealed that the sequence of HaVgR contained all of the conservative structural motifs of LDLR family members, and phylogenetic analysis indicated that HaVgR had a high identity among Lepidoptera and was distinct from that of other insects. Consistent with other insects, HaVgR was specifically expressed in ovarian tissue. The developmental expression pattern showed that HaVgR was first transcribed in the newly metamorphosed female adults, reached a peak in 2-day-old adults and then declined. Western blot analysis also revealed an ovarian-specific and developing expression pattern, which was consistent with the HaVgR mRNA transcription. Moreover, RNAi-mediated HaVgR knockdown strongly reduced the VgR expression in both the mRNA and protein levels, which inhibited the yolk protein deposition in the ovaries, led to the dramatic accumulation of vitellogenin and the up-regulation of HaVg expression in hemolymph, and eventually resulted in a declined fecundity. Together, all of these findings demonstrate that HaVgR is a specific receptor in uptake and transportation of yolk protein for the maturation of oocytes and that it plays a critical role in female reproduction.